Nodular amyloid goiter: a propósito de un caso - Calvelo, Agustín A; Falconi, Luis; Castiglioni, Dinorah (Cirugía del Uruguay, 1977)
The authors report a case of cold nodular goiter. After right subtotal lobectomy and resection of the isthinus, the pathologic diagnosis was amyloid nodule. The analysis of the bibliography demonstrate that amyloid goiter consecutive to· Amyloid disease is rare. The reasons fer surgical intervention are either the suspicion of primary malignancy in the thyroid gland or the severity of local manifestations. In the case presented, postoperative evaluation of basic amyloidosis was not possible.